Sex determination of Bangkok Zebra dove (Geopelia striata) based on wing and tail feather morphometrics at 3 and 6 months of age - Kamilah Nurizza; Yeni Dhamayanti; Epy Muhammad Luqman; Gracia Angelina Hendarti; Soeharsono Soeharsono; Boedi Setiawan (Ovozoa: Journal of Animal Reproduction, 2025)
This study aimed to determine the sex of Bangkok Zebra doves (Geopelia striata) based on external body morphometric measurements. A total of 32 doves were used, consisting of 16 females (8 bird each at 3 and 6 months of age) and 16 males (8 birds each at 3 and 6 months of age). Four morphometric parameters were measured: wing chord, antebrachium (forearm) length, longest primary feather, and longest tail feather. Wing and forearm lengths were measured using digital calipers with a precision of 0.01 mm, while the longest primary and tail feathers were measured using a ruler with 0.05 mm precision. The results showed that the average wing chord, longest primary feather, and longest tail feather lengths were significantly greater (p <0.05) in males compared to females. At six months of age, males also had a significantly longer forearm than females (p <0.05). However, no significant difference (p >0.05) was found in forearm length between sexes at three months of age. It could be concluded that wing and tail feather morphometrics can be used to distinguish between male and female Bangkok Zebra doves at both three and six months of age, except for forearm length at three months.